Karakteristik dan pelepasan asam salisilat dari sediaan nanogel secara in vitro - Nurul Arafah; Minda Sari Lubis; Rafita Yuniarti; Zulmai Rani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Salicylic acid is a beta-hydroxy acid (BHA) widely used in dermatology due to its keratolytic, comedolytic, and anti-inflammatory properties. Aim: This study aims to determine the amount of salicylic acid active ingredient incorporated into the nanogel formulation and to assess whether the salicylic acid active ingredient in the nanogel formulation can enhance the rate of release through the skin barrier. Methods: formulation of a nanogel preparation containing 1% salicylic acid. Subsequently, particle size measurements, determination of salicylic acid concentration, absorption efficiency testing, and release testing were conducted in vitro using a Franz diffusion cell, thereby allowing the determination of the cumulative amount of salicylic acid released and its flux. Results: The salicylic acid nanogel formulation has a particle size of 46.8 nm, indicating successful nanogel formation. The average adsorption efficiency value from six replicates was 92.8%, indicating that most of the salicylic acid was successfully adsorbed into the nanogel system. In vitro release tests showed an increase in cumulative release as samples were taken from minute 15 to minute 480, yielding an average Q value of 17.9 ± 0.08 µg/cm² and continuing to rise to 86.4 ± 0.08 µg/cm². Conclusion: A salicylic acid nanogel formulation has the potential to enhance the effectiveness of topical salicylic acid delivery.